DAMPAK KUALITAS PENDIDIKAN TERHADAP PENGEMBANGAN KETERAMPILAN SUMBER DAYA MANUSIA - Sulfiani, Besse; Rahmatilla; Tenri Rina Armita, Andi; Soraya, Ayu; Edi, Muhammad; Darul Aksa, Baso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is the main foundation in the development of a nation, playing an important role in forming competent human resources (HR) who are ready to compete in the global era. This article explores the relationship between the quality of education and the development of HR skills, highlighting the importance of education that is relevant, inclusive, and adaptive to the needs of the labor market. Through a descriptive qualitative approach and literature study, this study found that good quality education not only improves individual abilities, but also contributes to economic growth, social welfare, and poverty alleviation. Challenges faced in improving the quality of education, such as limited resources and teacher quality, need to be addressed through increasing the education budget and continuous training for teachers. The results of this study are expected to provide significant contributions to policy makers and practitioners in formulating strategies to improve the quality of education, so as to create a productive, innovative, and competitive workforce. Thus, investment in quality education is a must to drive the nation's progress in the long term.